Adjuvant therapy with high dose vitamin D following primary treatment of melanoma at high risk of recurrence: a placebo controlled randomised phase II trial (ANZMTG 02.09 Mel-D) - Saw, Robyn PM (BMC Cancer, 2014)
BACKGROUND: Patients with primary cutaneous melanomas that are ulcerated and >2 mm in thickness, >4 mm in thickness and those with nodal micrometastases at diagnosis, have few options for adjuvant treatment. Recent studies have suggested a role for vitamin D to delay melanoma recurrence and improve overall prognosis. METHODS/DESIGN: This is a pilot placebo-controlled randomised phase II trial to assess the feasibility, safety and toxicity of an oral loading dose of Vitamin D (500,000 IU) followed by an oral dose of 50,000 IU of Vitamin D monthly for 2 years in patients who have been treated for cutaneous melanoma by wide excision of the primary. Patients aged 18 – 79 years who have completed primary surgical treatment and have Stage IIb, IIc, IIIa (N1a, N2a) or IIIb (N1a, N2a) disease are eligible for randomisation 2:1 to active treatment or placebo. The primary endpoints are sufficiency of dose, adherence to study medication and safety of the drug. The secondary endpoints are participation and progression free survival. The study has been approved by the Ethics Review Committee (RPAH Zone) of the Sydney Local Health District, protocol number X09-0138. DISCUSSION: Effective, non-toxic adjuvant therapy for high risk primary melanoma is not currently available. Favorable outcomes of this phase II study will form the basis for a multi-centre phase III study to assess whether the addition of oral high-dose vitamin D therapy in patients who have completed primary treatment for melanoma and are at high risk of recurrence will: 1. prolong time to recurrence within 5 years; 2. improve overall survival at 5 years and 3. be both safe and tolerable. 62 patients have been randomised since the study commenced in December 2010. Target accrual for the study has been met with 75 patients randomised between December 2010 and August 2014. The Mel-D trial is conducted by the Australia and New Zealand Melanoma Trials Group (ANZMTG 02.09) TRIAL REGISTRATION: Australia and New Zealand Clinical Trials Registry (ANZCTR) ACTRN12609000351213